Operative techniques in joint reconstruction surgery - Su, Edwin P.; Jerabek, Seth (Lippincott Williams & Wilkins, 2022)
"Derived from Sam W. Wiesel and Todd J. Albert's four-volume Operative Techniques in Orthopaedic Surgery, this single-volume resource contains a comprehensive, authoritative review of a full range of joint reconstruction surgical procedures. In one convenient place, you'll find the entire Adult Reconstruction section, as well as relevant chapters from the Trauma section of Operative Techniques in Orthopaedic Surgery. Superb full-color illustrations and step-by-step explanations help you master surgical techniques, select the best procedure, avoid complications, and anticipate outcomes. Written by global experts from leading institutions, Operative Techniques in Joint Reconstruction Surgery, Third Edition, clearly demonstrates how to perform the techniques, making this an essential daily resource for residents, fellows, and practitioners"--